Co-infection risk assessment of Giardia and Cryptosporidium with HIV considering synergistic effects and age sensitivity using disability-adjusted life years. (15th May 2020) - Han, Mingyi; Xiao, Shumin; An, Wei; Sang, Chenhui; Li, Hongyan; Ma, Jinfeng; Yang, Min
Abstract: Co-infection with multiple pathogens, especially the spread of Giardia and Cryptosporidium in source water among those with immunodeficiency, is common worldwide, which will result in an increase in overall risk. In this study, the quantitative microbial risk assessment model was used to estimate the cumulative risk of co-infection with Giardia and Cryptosporidium promoted by HIV, considering age sensitivity. The sensitivity of population segments with different ages was estimated by the optimization method, based on clinical data of cryptosporidiosis and giardiasis with age structure. The factors of co-infection enhancement were used to quantify HIV synergism with the action of other pathogens. The removal rates of Giardia and Cryptosporidium through water treatment were estimated by a model involving turbidity and particles. The results showed that children (0–4 years) were 17.911-fold more sensitive to infection with Giardia than adults (15–64 years), and that with Cryptosporidium was 10.592-fold. Removal rates of these parasites in water treatment plants in major cities in China were estimated to be 2.03 log10 . Considering the HIV-synergistic and age-susceptibility effects, the cumulative risk of exposure to Giardia or Cryptosporidium was about 38.781 × 10 −6 DALYs (Disability-adjusted life years) per person per year, which was much higher than the reference risk level recommended by the World Health Organization (10 −6 DALYs ). The methodology and results of this study will be useful in better evaluating and reducing the burden due to infection of Giardia and/or Cryptosporidium in China and other countries. Graphical abstract: Image 1 Highlights: Children were 17.9 fold more sensitive to infection with Giardia than adults. Children were 10.6 fold more sensitive to infection with Cryptosporidium than adults. Co-infection risk of those for immunodeficiency was much higher than that of previous. Removal rates of the particles in water treatment plants in China was 2.03 log10 .